Penerapan Lean manufactturing Berbasis Value Stream Mapping (VSM), Failure Mode and Effect Analysis (FMEA) Untuk Mengurangi Downtime Cleaning dan Penggunaan Sodium Hydroxide di PT TES - Baharui Gea; Sita Kurniaty Ratoko; Rakay Edhiargo Toyosito; Lifia Citra; Abimanyu Abimanyu (UNISTEK, 2026)
The Cleaning In Place (CIP) process on Line 1 plays an important role in maintaining equipment cleanliness and ensuring product safety. However, excessive Cleaning Downtime increases production Downtime and Sodium Hydroxide (NaOH) consumption. This study aims to identify waste in the CIP process, determine the main causes of excessive Cleaning Downtime, and develop and implement improvement Actions to enhance Cleaning effectiveness. The methods used include Value Stream Mapping (VSM), Fishbone Diagram, Failure Mode and Effects Analysis (FMEA), and 5W1H. VSM results indicated that Cleaning Activities were classified as Non-Value-Added (NVA) Activities and significantly contributed to Downtime. FMEA identified the main causes of excessive Cleaning Downtime as the absence of nozzle valve covers (RPN=512), elevated machine positions that hinder inspections (RPN=448), insufficient awareness briefings (RPN=392), CIP frequency based on routine prActices (RPN=294), and the absence of NaOH usage records (RPN=252). Improvement Actions were developed using the 5W1H method and implemented through the installation of nozzle valve covers, CIP effectiveness verification, team awareness briefings, revision of the CIP matrix frequency, and NaOH usage monitoring. The implementation results showed that Cleaning frequency decreased from two times to one time per month, Cleaning Downtime decreased from 45.33 hours to 22.67 hours per month, and NaOH consumption decreased from 300 kg to 150 kg per month. These improvements successfully enhanced Cleaning effectiveness and chemical usage efficiency.